PERANAN UNIT KELUARGA SEBAGAI BASIS PENDIDIKAN MENURUT PERSPEKTIF AL – QUR’AN - Indah Citra Soleha; Ahda Khilwa Sabrina; Elfiana; Hafizoh Halim; Nurhafidzah Arabella; Sangkot Abdullah Effendi Harahap (STKIP Subang, 2026)
The family serves as the initial and primary environment for a child’s education, laying the groundwork for personality development. In the Islamic perspective, the family functions as a central institution for instilling values, with the Qur’an highlighting the crucial role of parents in fostering faith, moral conduct, and ethical responsibility from an early age. Rapid social changes and technological advancements in recent years have influenced children’s learning patterns, making it increasingly important to strengthen the educational function of the family. This study aims to explore the role of the family as a Qur’anic-based educational foundation by reviewing relevant scholarly literature from the past five years. A descriptive qualitative approach was applied through a literature review, examining Qur’anic verses that address family education especially in modeling behavior, creating habits, and providing guidance as well as analyzing national and international research on Islamic education. The results indicate that the family acts not merely as a channel for knowledge transfer but also as a vital medium for character building and the cultivation of religious, moral, and social values. Evidence from recent studies demonstrates that proactive parental involvement significantly enhances children’s spiritual growth, behavior, and academic achievement. Consequently, reinforcing the family’s role as a Qur’anic educational base is imperative in addressing the challenges of contemporary education.